Outback : journey through northwest Australia [videorecording (DVD)] - Smith, Mark Coles, 1987-; Looby, Tosca; Bell, Paul (PBS, 2018)
In a landscape so ancient that, in parts, it predates life on the planet, are animals superbly adapted to the harsh and beautiful extremes of Outback Australia. Over the course of a year, journey with the people and animals of Australia's Kimberley region in northwest Australia: a vast, rugged and remote wilderness, bursting with character.-- Adapted from container.